Zoo-heleoplankton structure in three artificial ponds of North-eastern Argentina - M. Frutos, S.; Carnevali, R. (Revista de Biología Tropical, 2008)
The aim of the present study was to compare the abundance and species richness of zoo-heleoplankton bigger than 53 µm in an annual cycle under similar climate conditions in three artificial ponds, in order to observe the changes during an annual cycle. Samples were taken monthly from June 1993 to July 1994 in Corrientes, Argentina. The first pond (A) was covered an 80% by Eichhornia crassipes (Mart.), the second one (B) with bloom of Microcystis aeruginosa (Kurtzing) and the last one (C) with organic matter deposited in the bottom. The water was more acidic at pond A, and the water at pond B contained more dissolved oxygen concentration than the water at the other two ponds. The zoo-heleoplankton densities varied between 20-1728 ind.l-1 at pond A, 42-4082 ind.l-1 at pond B and 148-2447 ind.l-1 at pond C. The maximum zoo-heleoplankton abundance was found in the pond with cyanobacteria bloom during Autumn 1994 and the minimum abundance was found in the one with a predominance of E. crassipes. The rank of species richness was pond A > pond B > pond C. Rotifera was the most abundant group in pond A whereas the larval stages of Copepoda were abundant in the other two ponds. Anuraeopsis navicula Rousselt 1910 was the dominant population in the pond with macrophytes prevalence. Brachionus calyciflorus Pallas 1776 and larval stage of Copepoda had variable proportions in the pond with cyanobacteria bloom. Thermocyclops decipiens (Kiefer 1929) was present during the annual cycle only in the pond with organic matter deposited in the bottom. The succession of taxa was observed in the pond with coverage of aquatic macrophytes and with cyanobacteria bloom. Differences in species richness and low similarity in zoo-heleoplankton between ponds were determined by differences in the quality of the water in relation to the presence of macrophytes, cyanobacteria, organic matter deposited in the bottom and fish predation. Multiple regression analysis (stepwise) revealed that water transparency, dissolved oxygen and conductivity were the environmental variables that explained more than 42% of variability in the abundance of the dominant species.